2009
DOI: 10.1002/jor.20857
|View full text |Cite
|
Sign up to set email alerts
|

FGF23 is a putative marker for bone healing and regeneration

Abstract: Besides numerous other factors, fibroblast growth factor receptor (FGFR) signaling is involved in fracture healing and bone remodeling. FGF23 is a phosphatonin produced by osteoblastic cells, which signals via FGFR1, thereby exerting effects in bone and kidney. We analyzed if serum FGF23 levels might be an indicator to predict fracture healing and union. FGF23 (C-Term) was elevated on day 3 postoperatively in 55 patients sustaining an exchange of total hip implants due to aseptic loosening. A prospective study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 43 publications
3
37
1
Order By: Relevance
“…Chondrogenesis and subsequent chondrocytic proliferation and differentiation are regulated by Wnt/ FGF23; instead, fibroblastic cells in the bone marrow became FGF23-positive as early as post-fracture day 4, remaining so throughout post-fracture week 3. Goebel et al have reported that FGF23 was synthesized in the granulation tissues surrounding bone fracture sites, suggesting that FGF23 is a possible parameter for bone healing (12). In our study, FGF23-producing fibroblastic cells were seen early in the bone marrow, and were still present in the granulation tissue 3 weeks after the fracture.…”
Section: Histological Alteration and Immunolocalization Of Sclerostinsupporting
confidence: 63%
“…Chondrogenesis and subsequent chondrocytic proliferation and differentiation are regulated by Wnt/ FGF23; instead, fibroblastic cells in the bone marrow became FGF23-positive as early as post-fracture day 4, remaining so throughout post-fracture week 3. Goebel et al have reported that FGF23 was synthesized in the granulation tissues surrounding bone fracture sites, suggesting that FGF23 is a possible parameter for bone healing (12). In our study, FGF23-producing fibroblastic cells were seen early in the bone marrow, and were still present in the granulation tissue 3 weeks after the fracture.…”
Section: Histological Alteration and Immunolocalization Of Sclerostinsupporting
confidence: 63%
“…FGF23 Cterminal enzyme-linked immunosorbent assay (ELISA) yields the sum of the C-terminal fragment and intact FGF23 [74,75] , whereas FGF23 intact ELISA simply yields iFGF23, which constitutes the biological activity of FGF23 and is involved in pathophysiological processes in subjects with CKD and other phosphatemic disorders [74,76,77] . Animal studies have shown that an increase in cFGF23 by C-terminal ELISA may be due to the increase in C-terminal fragments acting as an acute-phase reactant under stressful conditions because iFGF23 was not elevated [78] . This concept in CKD patients is still uncertain and needs to be confirmed.…”
Section: High Fgf23 In Ckdmentioning
confidence: 99%
“…Recent studies indicate that FGF23 is increased in callus during fracture healing, consistent with local matrixderived FGF23-stimulating factors [110]. It is also possible that the discrepancies between PTH lack of a direct effect on FGF23 promoter activity and the 42.…”
Section: Osteocyte Production Of Fgf23 Coordinates Renal Phosphate Hamentioning
confidence: 92%